THE FUNDAMENTAL RIGHT TO PRIVACY IN BRAZIL AND THE INTERNET PRIVACY RIGHTS IN REGULATING PERSONAL DATA PROTECTION - Fortes, Vinícius Borges; Oro Boff, Salete; Galindo Ayuda, Fernando (Revista Eletrônica do Curso de Direito da UFSM, 2016)
The Brazilian Constitution, Article 5, paragraph X, ensure the inviolability of privacy, intimacy and honour as a fundamental right. The Brazilian Internet Bill of Rights, called ‘Marco Civil da Internet’, instituted in Brazil diversity of principles and parameters for regulation of internet in the country. The existence of the gap in the Brazilian legal system, around laws and infrastructure for the effective guarantee to the right to data protection on the Internet, as identified in other countries, coupled with the absence of specific conceptual precision to privacy on the internet, justifies the adoption in this research, the innovative concept of ‘Internet Privacy Rights’, based on Bernal (2014), composed of four rights-based: a right to roam the internet with privacy; a right to monitor those who monitor us; a right to delete personal data; a right to an online identity. This research has the overall objective to propose a conceptual incorporation, explicit and expressed, of Internet Privacy Rights as one of the pillars to ensure greater extent on the effectiveness of the fundamental right to privacy, particularly in Brazilian process of creation of laws, related to the protection of personal data on the internet. This research uses the methods of comparative and historical procedure in order to establish relationships and analysis within the historicity linked to aspects of the internet and Law, the evolution of fundamental rights to the effective recognition of privacy as a right. The research uses the hypothetical-deductive method of approach, with theoretical evidence, ranging from general aspects to the most specific, building the theoretical framework that allowed and confirm or refute the preliminary hypotheses and presented as the problem solving possibilities. The type of developed research was qualitative and exploratory nature, associated with the technical of review and literature analysis, covering the query varied references, allowed the construction of the results presented in the research, particularly the proposed conceptual incorporation. The study concludes that the express reception of Internet Privacy Rights by the laws that deal and also will address related topics in Brazil, especially those which regulate or will regulate the protection of personal data in the country, allows the recovery of the core of the fundamental right to privacy that, according to the theories presented in this research, only the protection of private life, honour, intimacy and image are considered. The research embodies a theoretical and conceptual construction to support the premise that the Internet Privacy Rights are included in the core of the fundamental right to privacy, which is why they deserve the explicit and express incorporation into legal rules, that in one imminent way, will regulate, in the context of the Internet, the fundamental right to privacy and protection of personal data in Brazil.